PENINGKATAN SUMBER DAYA EKONOMI PETERNAK KELINCI DI KEDIRI MELALUI PERBAIKAN MANAJEMEN PAKAN DAN PRODUKSI - Sigit, Miarsono; Wika Adi Pratama, Junianto; Wardhani, Hana Cipka Pramuda; Nur Ardiansyah, Ferdi (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Kediri is a densely populated city that has problems regarding livestock. The problems that are often experienced are the land for raising livestock and the availability of feed. Raising rabbits is one of the ways used by the Sumber Rejeki livestock group in Kediri. Rabbits can digest various types of feed, so that it can facilitate the maintenance process, especially in the Kediri area which utilizes local feed resources. Rabbits have good potential and can be superior in terms of reproduction and production. The hope is that with rabbit cultivation, group members will be able to improve the economy and nutritional value of the family or the wider community. Constraints that are often experienced by rabbit breeders are the number of puppies that are relatively low in each period, the mortality rate is quite high in puppies and adult rabbits due to frequent bloating and diarrhea, and the lack of information about the local waste that can be used as feed for rabbits. Lack of knowledge in preparing rations for rabbits at each different phase, and lack of knowledge about online marketing. The solution that is expected is to carry out training on proper rabbit cultivation, pregnancy checks, counseling on handling forage, and training members of livestock groups to prepare rabbit rations. Additional provision of complete feed ingredients for rabbits supplemented with cabbage leaves, moringa leaves, and sengon leaves as well as pollard, rice bran, copra meal, soybean meal, drops, and mineral salts. And don't forget to teach marketing of their products in the form of rabbits and biscuits for rabbits online in electronic media and market places. The resulting outputs include increasing the number of children in the next period, reducing the mortality rate of rabbits, and making biscuit-shaped feed so that it is easier to bite and can be consumed by other rodents. This feed product will later be referred to as rabbit bio supplement biscuits. Making rations for weaning rabbits and brooders.